Sidi Muhammad Ben Badis (d. 1388 AH) and his position on samāʿ (oral transmission/hearing in linguistic authority) - Al-Qaim, Mohamed; Bkader, Abdelkader (El Omda in Linguistics and Discourse Analysis, 2025)
In this research paper,we will try to understand Ibn Badi’s attitude or opinion about listening in which I discussed the personality of the Sheikh and his effects, indicating the sources of listening that he relied on in grammatical citation, and his attitude or opinion on each of them, trying to represent that. The study concluded that listening is one of the principles of grammar according to Ibn Badi, as he cited more than the words of the Arabs in poetry and prose, and also cited the Holy Qur’an and the Noble Hadith, In this, he was not an innaovation, but rather followed what his predecessors had followed, while he reduced the citation of the Hadith.It is not forbidden to quote it, but it is considered permissible to do so .